Extraosseous Ewing sarcoma of pancreas: a rare entity - Abdullah, Maizaton Atmadini; Abd Ghani, Fauzah; Mohamed Shabery, Noor Afidah; Sulaiman, Nor Akmar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Ewing sarcoma is a rare type of cancer that typically arises in the bones or soft tissues of children and young adults. However, Ewing sarcoma can also occur in other body parts, including the pancreas. Ewing sarcoma of the pancreas is rare and often affects children or young adults. We reported a 33-year-old male with no medical illness who presented with worsening epigastric pain and vomiting for one-week duration. CT scan of the abdomen showed an obstructive duodenal mass complicated with perforation. The biopsy of the duodenal mass showed sheets of small round blue cells with immunohistochemical features favouring Ewing sarcoma. Pancreatoduodenectomy procedure (Whipple resection) was performed, which revealed an ill-defined whitish solid tumour at the head of the pancreas measuring 80x50x65mm. Histologically, the tumour is composed of sheets of malignant cells displaying uniform small round to oval nuclei containing fine chromatin, inconspicuous nucleoli, scanty cytoplasm, and indistinct cell membrane. A few mitoses are seen (4/10HPF). Areas of tumour necrosis are observed. Scattered lymphovascular invasion is also present. The malignant cells are infiltrating into the duodenal mucosa. The malignant cells are diffuse and strongly positive towards CD99, FLI-1 and NK2.2 (Figure 3). A diagnosis of primary pancreatic Ewing sarcoma was made.